2020
DOI: 10.1111/ahe.12537
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of human umbilical cord mesenchymal stem cell into germ‐like cell under effect of co‐culture with testicular cell tissue

Abstract: Supplements produced by mouse testicular cells (mTCs) and the interaction between cells can increase the differentiation rate of human umbilical cord mesenchymal stem cells (hUCMSCs) into the germ‐like cells. We studied the differentiation rate of hUCMSCs into the germ‐like cells under effect of mTCs co‐culturing. Isolated hUCMSCs from postpartum human umbilical cords were cultured. Then, the expression of mesenchymal (CD73, CD90 and CD105) and haematopoietic (CD34 and CD45) markers of hUCMSCs were confirmed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Coculture with mouse testicular cells promotes the differentiation of human MSCs from the umbilical cord into germ-like cells. 72 These studies illustrate that Sertoli cells and the testicular cells may provide the niche, which facilitates the differentiation of MSCs into male germ cells. The combination of RA with Sertoli cells-conditioned medium is employed as the stimulator to evaluate the MSC differentiation ability, 73 – 76 while RA and testosterone have been shown to enhance male germ-like cell formation from adipose-derived MSCs when cocultured with Sertoli cells in vitro .…”
Section: Derivation Of Male Germ Cells From the Mscsmentioning
confidence: 90%
“…Coculture with mouse testicular cells promotes the differentiation of human MSCs from the umbilical cord into germ-like cells. 72 These studies illustrate that Sertoli cells and the testicular cells may provide the niche, which facilitates the differentiation of MSCs into male germ cells. The combination of RA with Sertoli cells-conditioned medium is employed as the stimulator to evaluate the MSC differentiation ability, 73 – 76 while RA and testosterone have been shown to enhance male germ-like cell formation from adipose-derived MSCs when cocultured with Sertoli cells in vitro .…”
Section: Derivation Of Male Germ Cells From the Mscsmentioning
confidence: 90%
“…Female [158] RA and Sertoli cell-conditioned medium induced GCs positive for Prm1 and Stra8 Male [229] RA and Sertoli cell-conditioned medium triggered the differentiation of GCs with diminished Oct4 and PLZF expression and upregulated ACR, Prm1, Stra8, and SYCP3. Some secondary spermatocytes and spermatidlike cells developed Male [230] BMP4/RA and polarized or non-polarized red light irradiation induced Dazl, Fragilis, SYCP3, and Vasa expression Male [231] Follicular fluid and cumulus cells-conditioned medium triggered the development of oocyte-like cells positive for c-Kit, Gdf9, SYCP3, Vasa, ZP1, ZP2, and ZP3 Female [232] Co-cultivation with testicular cells induced Fragilis, SYCP3, and Vasa-positive GCs Male [233] like RNA-mediated gene silencing 2 protein (Piwil2), protamine 1 (Prm1), Stella (also known as developmental pluripotency associated 3 protein), the protein Stra8 stimulated by retinoic acid, the synaptonemal complex protein 3 (SYCP3), Vasa (also designated DDX4-DEAD-box helicase 4), or the zona pellucida sperm-binding proteins ZP1, ZP2, and ZP3. Using such approaches, a variety of different studies already demonstrated the successful development of multipotent stem cells derived from amniotic fluid, amniotic membrane, chorion leave, and Wharton´s jelly into female and male germ cells (Table 2 and references cited therein).…”
Section: Amniotic Fluidmentioning
confidence: 99%